2021
DOI: 10.3390/medicina57090964
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Clostridioides difficile Infection in Cirrhotic Patients Receiving Norfloxacin for Secondary Prophylaxis of Spontaneous Bacterial Peritonitis—A Real Life Cohort

Abstract: Background and Objectives: Spontaneous bacterial peritonitis (SBP) is a life-threatening complication of liver cirrhosis. Antibiotic prophylaxis is effective but can lead to an increased incidence of Clostridioides difficile infection (CDI). The aim of this study was to evaluate the incidence of CDI and the risk factors in cirrhotic patients with a previous episode of SBP receiving norfloxacin as secondary prophylaxis. Materials and Methods: We performed a prospective, cohort study including patients with live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Norfloxacin prophylaxis is reported to be associated with three major adverse outcomes: increased risk of infections by gram-positive organisms [16], increased risk of Clostridium difficile infections [105], and lastly, increased risk of development of MDROs [16,106,107].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Norfloxacin prophylaxis is reported to be associated with three major adverse outcomes: increased risk of infections by gram-positive organisms [16], increased risk of Clostridium difficile infections [105], and lastly, increased risk of development of MDROs [16,106,107].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a small prospective study conducted in Romania in 2015, among 200 Child-Pugh B and C patients hospitalized for decompensation, 9% developed CDI during their hospitalization [ 36 ]. Another prospective study, also conducted in a Romanian tertiary hospital, included 122 patients with cirrhosis and spontaneous bacterial peritonitis (SBP) who also received norfloxacin as secondary prophylaxis from 2018 to 2019, in which 18.8% of the population presented with CDI (median follow-up of 7 months) [ 37 ]. In a further over six years study, CDI incidence was 11.8% in 388 cirrhotic patients, and notably, 30.8% of the cirrhotic patients received the antibiotic rifaximin to prevent HE [ 38 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Age >65 years, multiple hospitalizations, inpatient stays >20 days, hypoproteinemia, Clostridioides difficile colonization (CDC), HE, antibiotic, and proton pump inhibitors (PPIs) use were found to be associated with the development of CDI in a study conducted to identify risk factors for CDI in patients with cirrhosis [ 45 ]. Furthermore, many studies have also reported risk factors for CDI development [ 22 , 23 , 30 , 32 , 35 , 37 , 39 , 46 49 ] although heterogeneity exists between studies. The risk factors concluded from these studies are largely in line with the previous research and can be broadly classified into several categories, namely medications (PPIs, antibiotics, etc.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations